Digital Image Watermarking Using Arnold Scrambling and Berkeley Wavelet Transform - Alwan, Iman M.G.; Jamel, Enas Muzaffer (Al-Khwarizmi Engineering Journal, 2017)
Embedding an identifying data into digital media such as video, audio or image is known as digital watermarking. In this paper, a non-blind watermarking algorithm based on Berkeley Wavelet Transform is proposed. Firstly, the embedded image is scrambled by using Arnold transform for higher security, and then the embedding process is applied in transform domain of the host image. The experimental results show that this algorithm is invisible and has good robustness for some common image processing operations.